THE AUDIT COMPUTER BASED ACCOUNTS - المكي , محمد (Dirasat in Economics and Business, 1978)
The old auditing procedures and techniques cannot be used in practice when computer based accounts are involved. The two main reasons for this are . 1) The data and information are mainlv available in machine sensible form. 2) Computer records of many sections of the accounts and financial information are never printed out. However the duties and responsibilities of the auditor are the same as they are in the conventional type of' audit. To counter some of the problems in auditing created bv the introduction of the auditor may follow the following cheks • 1.Check on planning of the system, i.e study the system involved. 2.Test and verify internal control and other controls - financial, operational, internal check and administrative controls. 3.Check the input-the data to be processed. 4.Check the output - the product of processed data. 5.Other check and tests, e.g. a)Standing data retained in the computer. b)Control totals, etc.